PERAN ROTASI DAN MUTASI KERJA TERHADAP KINERJA KARYAWAN DI 4 (EMPAT) PERUSAHAAN IMPOR AREA JAKARTA UTARA PADA TAHUN 2020 - Zamroni (Sekolah Tinggi Ilmu Ekonomi Tribuana, 2020)
This study aims to explain the alleged relationship between job rotation and job transfer on employee performance in 4 import companies in North Jakarta. The sample data taken was 96 respondents. By using the Structural Equation method or SEM the data processing and analysis were carried out. The findings of this study indicate that there is a significant positive relationship between employee rotation and employee performance partially, but it does not show a significant effect on employee transfer on employee performance.